Review of the research on the influence of different functional substituents of new 1,2,4-triazole derivatives on the compounds biological properties - M. V. Ogloblina; I. V. Bushueva; V. V. Parchenko (The State Expert Center of the Ministry of Health of Ukraine, 2022)
Today, 1,2,4-triazole derivatives are a promising class of organic compounds. This is caused, first of all, by the possibility of various chemical modifications of the 1,2,4-triazole fragment due to the addition of typical pharmacophores, which contributes to the expansion of the new molecules' arsenal. A significant number of the 1,2,4-triazole derivatives show biological properties, that postively affects the further process of the most promising substances' introduction. The aim of the work was to analyze the influence of various functional substituents of the new 1,2,4-triazole derivatives on the indicators of the mentioned compounds' biological activity. Literature sources containing information on the influence of various functional substituents of the new 1,2,4-triazole derivatives on the indicators of these compounds' biological activity became the research materials. Methods were used in the work: analytical, bibliosemantic information search, generalization. Triazoles and their heterocyclic analogues are compounds that contain a certain amount of Nitrogen atoms in their composition, showing the properties of typical pharmacophores. Their derivatives are easily synthesized and can be transformed into various biologically active molecules. Information on the 1,2,4-triazole derivatives' chemical modeling, which allows for purposefully obtaining compounds with the necessary biological properties, taking into account the toxicity indicators of new molecules, has been analyzed and summarized. The authors have proved, that the gradual and predicted introduction of various substituents into the molecule of 1,2,4-triazole derivatives leads to the appearance of new types of biological activity, in some cases it gives an increase in already existing activity indicators. Chemical compounds' modification due to the substituents' changing around the 1,2,4-triazole fragment fundamentally changes the type of biological activity of new molecules. This approach was chosen by the majority of scientists as promising one for the new biologically active substances' search among the 1,2,4-triazole derivatives. The priority, relevance and perspective of such researches have been proved by not only domestic scientists' teams. Recently, foreign investigators from Turkey, India, Korea, China, Egypt, etc. have been actively searching for new biologically active substances among the 1,2,4-triazole derivatives. The analysis of modern literary sources on the study of the new 1,2,4-triazole derivatives' biological activity allows us to establish certain features of the various functional substituents' influence on the types of biological activity and convincingly proves the outlook of further synthetic tests in the compounds' specified series.